The Accuracy of Endodontic Length Measurement Using Cone-beam Computed Tomography in Comparison with Electronic Apex Locators - Pham, Khoa Van; Khuc, Ngan Kim (Iranian Endodontic Journal, 2020)
Introduction: The aim of this in vitro study was to evaluate the accuracy of cone-beam computed tomography (CBCT) and two electronic apex locators (EALs) when measuring the actual length of root canals. Methods and Materials: One hundred and eighty four root canals in 135 extracted anterior and posterior permanent teeth were studied. Root canal curvatures were analyzed on CBCT images, and root canals with curvatures less than 70º were chosen. Root canal length measurements were performed using CBCT, ProPex Pixi, E-Pex Pro, and the actual length (AL). The percentages of the measurements in the range of ±0.5 mm to the AL were compared using Fisher’s Exact test. The ICC indices and Bland-Altman plots were used to display the agreement of three devices with the AL measurements. The statistical significance was set at P<0.05. Results: The accuracies of E-Pex Pro and ProPex Pixi (87.5% and 82.6%, respectively) were better than that of CBCT (71.7%) (P<0.05). Conclusion: This in vitro study showed that although the accuracies of the two EALs were at high level, there was no device that had an agreement with the actual root canal length measurement Keywords:Cone-beam Computed Tomography; Electronic Apex Locator; Endodontics; Root Canal Length; Root Canal Therapy